THE DYNAMICS OF MUSLIM WOMEN IN MINORITY AREAS: PERCEPTIONS OF HIJAB USAGE (INTERNATIONAL SEMINAR, 2024)
The hijab, as a symbol of identity and modesty in Islam, often becomes a subject of debate involving religion, culture, and individual freedom while facing challenges such as discrimination and stereotypes in predominantly non-Muslim societies. This study aims to explore the perceptions, motivations, and self-views regarding the hijab among Muslim women living in minority regions. Using a qualitative method, the research involved 20 Muslim women who consistently wear the hijab in their daily lives. Data were collected through a survey consisting of three closed-ended questions and analyzed using pie charts to illustrate the distribution of responses. The findings reveal that the majority of participants (55%) view the hijab as a symbol of identity, with personal comfort and individual preference (55%) being the primary reasons for wearing it, followed by social factors and family expectations (30%). Moreover, the hijab is perceived as a tool for reinforcing self-identity and coping with social pressures, despite its association with challenges such as discrimination and prejudice. This study provides insights into the profound meaning of the hijab for Muslim women in minority areas, highlighting its role not only as a religious symbol but also as a crucial element in shaping personal and social identity.